2020
DOI: 10.1016/j.cell.2020.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Humoral Functional Evolution Tracks with SARS-CoV-2 Mortality

Abstract: The urgent need for an effective SARS-CoV-2 vaccine has forced development to progress in the absence of well-defined correlates of immunity. While neutralization has been linked to protection against other pathogens, whether neutralization alone will be sufficient to drive protection against SARS-CoV-2 in the broader population remains unclear. Therefore, to fully define protective humoral immunity we dissected the early evolution of the humoral response in 193 hospitalized individuals ranging from moderate-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
371
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(396 citation statements)
references
References 47 publications
24
371
0
1
Order By: Relevance
“…Recent studies have examined Fc-mediated effector functions of antibodies elicited upon SARS-CoV-2 infection (19, 32). Both the presence of IgG and their Fc-mediated effector activities have been linked to reduced severity of disease (21). Herein, we assessed the ability of plasma from convalescent donors to trigger ADCC responses over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have examined Fc-mediated effector functions of antibodies elicited upon SARS-CoV-2 infection (19, 32). Both the presence of IgG and their Fc-mediated effector activities have been linked to reduced severity of disease (21). Herein, we assessed the ability of plasma from convalescent donors to trigger ADCC responses over time.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, in addition to neutralizing viral particles, the antiviral activities of SARS-CoV-2-specific antibodies can expand to involve Fc-effector functions, including antibody-dependent cellular cytotoxicity (ADCC) (19, 20). Recent research has highlighted the importance of humoral development and the ability of antibodies to carry out Fc-effector functions in decreasing mortality of patients exhibiting severe disease symptoms (21).…”
Section: Introductionmentioning
confidence: 99%
“…It is 298 hypothesized that sIgA mainly protects the upper respiratory tract, whereas systemic IgG 299 protects the lower respiratory tract 14,27,28 . 36 . A recent study in mice demonstrated that in vitro neutralization did not uniformly correlate with in vivo protection, and that binding to Fc receptors was of importance, suggesting that antibody effector functions play a pivotal role in protection against SARS-CoV-2 37 .…”
Section: Figure 1 Sars-cov-2 Challenge Of Syrian Hamsters Vaccinatedmentioning
confidence: 99%
“…In a study to dissect early evolution of the antibody responses in COVID-19 patients with different severities, robust IgA and IgM antibody responses were found in both survivors and non-survivors (Zohar et al, 2020). However, antigen-specific IgG with compromised Fcγ receptor binding and Fc effector activity was found in non-survivors, suggesting defective humoral response that may be associated with worse disease outcome (Zohar et al, 2020) The kinetics of neutralizing activities of anti-SARS-CoV-2 antibodies in COVID-19 patients were measured using pseudotyped particles or native virus (Harvala et al, 2020;Ni et al, 2020;Prevost et al, 2020;Wang et al, 2020e;. Neutralizing antibodies developed within 2 weeks after disease onset and neutralizing activities significantly decreased after symptom resolution (Prevost et al, 2020).…”
Section: Structural and Neutralizing Properties Of Anti-sars-cov-2 Anmentioning
confidence: 99%